2013
DOI: 10.1111/1365-2664.12145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a multispecies adaptive management framework: must uncertainty impede effective decision‐making?

Abstract: Summary1. Application of adaptive management to complex natural resource systems requires careful evaluation to ensure that the process leads to improved decision-making. As part of that evaluation, adaptive policies can be compared with alternative nonadaptive management scenarios. Also, the value of reducing structural (ecological) uncertainty to achieving management objectives can be quantified. 2. A multispecies adaptive management framework was recently adopted by the Atlantic States Marine Fisheries Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Several efforts have occurred to develop horseshoe crab population models useful for assessing population viability (Gibson and Olszewski 2001;Grady and Valiela 2006;Davis et al 2006;Sweka et al 2007;McGowan et al 2011b;Smith et al 2013). Modeling studies have focused on horseshoe crab populations in Rhode Island (Gibson and Olszewski 2001), Cape Cod , and Delaware Bay (Davis et al 2006;Sweka et al 2007;McGowan et al 2011b;Smith et al 2013).…”
Section: Population Viability Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several efforts have occurred to develop horseshoe crab population models useful for assessing population viability (Gibson and Olszewski 2001;Grady and Valiela 2006;Davis et al 2006;Sweka et al 2007;McGowan et al 2011b;Smith et al 2013). Modeling studies have focused on horseshoe crab populations in Rhode Island (Gibson and Olszewski 2001), Cape Cod , and Delaware Bay (Davis et al 2006;Sweka et al 2007;McGowan et al 2011b;Smith et al 2013).…”
Section: Population Viability Analysesmentioning
confidence: 99%
“…Modeling studies have focused on horseshoe crab populations in Rhode Island (Gibson and Olszewski 2001), Cape Cod , and Delaware Bay (Davis et al 2006;Sweka et al 2007;McGowan et al 2011b;Smith et al 2013). All analyses concluded that while high harvest results in population depletion, some Additional details can be found in Sweka et al (2013: Appendix B) Rev Fish Biol Fisheries (2017) 27:135-175 159 levels of reduced harvest can be compatible with maintenance of a viable population.…”
Section: Population Viability Analysesmentioning
confidence: 99%
“…[]; Smith et al. []; McGowan []). The framework presented here provides a tool that can be used in conservation decision making, but should also be continuously refined and tested as more information becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the Delaware Bay, red knots and other shorebirds feed predominantly on the eggs laid by spawning horseshoe crabs while they are available (Tsipoura and Burger, 1999;Mizrahi and Peters, 2009;McGowan et al, 2011;Smith et al, 2013). It is unlikely that other food sources found at shorebird stopover sites would be as widely available or as nutritionally dense as horseshoe crab eggs (Mizrahi and Peters, 2009).…”
Section: Shorebirds As Bellwethersmentioning
confidence: 99%